2015
DOI: 10.1021/acs.inorgchem.5b01706
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Structural Correlations in a Series of Pseudotetrahedral [CoII(XR)4]2–Single Molecule Magnets: An ab Initio Ligand Field Study

Abstract: Over the past several decades, tremendous efforts have been invested in finding molecules that display slow relaxation of magnetization and hence act as single-molecule magnets (SMMs). While initial research was strongly focused on polynuclear transition metal complexes, it has become increasingly evident that SMM behavior can also be displayed in relatively simple mononuclear transition metal complexes. One of the first examples of a mononuclear SMM that shows a slow relaxation of the magnetization in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
121
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 66 publications
14
121
2
Order By: Relevance
“…40 DFT calculations have been employed to extract J values in a linear {Mn II -Mn III -Mn II } cluster [Mn 3 (Hcht) 2 (bpy) 4 ] 3+ (11) (HCht=cis,cis-1,3,5-cyclohexanetriol; see Figure 4b). 45 46 It is worth to note here that this Mn 6 cluster broke the record U eff barrier of the classical Mn 12 Figure 6b) are given in Table 1 and they yield excellent fit to the susceptibility data (see Figure 6c). Calculations in this case clearly suggest that the nextnearest neighbour interactions cannot be neglected as it can be some time strong enough to compete with the nearest-neighbour interactions.…”
Section: Exploring Isotropic J In Mn Polynuclear Complexesmentioning
confidence: 73%
See 2 more Smart Citations
“…40 DFT calculations have been employed to extract J values in a linear {Mn II -Mn III -Mn II } cluster [Mn 3 (Hcht) 2 (bpy) 4 ] 3+ (11) (HCht=cis,cis-1,3,5-cyclohexanetriol; see Figure 4b). 45 46 It is worth to note here that this Mn 6 cluster broke the record U eff barrier of the classical Mn 12 Figure 6b) are given in Table 1 and they yield excellent fit to the susceptibility data (see Figure 6c). Calculations in this case clearly suggest that the nextnearest neighbour interactions cannot be neglected as it can be some time strong enough to compete with the nearest-neighbour interactions.…”
Section: Exploring Isotropic J In Mn Polynuclear Complexesmentioning
confidence: 73%
“…The D parameter is particularly associated with Spin-Orbit coupling (SOC), Spin-Spin coupling (SSC) and structural distortion 12 observed in the coordination sphere (such as Jahn-Teller distortion; J-T). These parameters stabilize energy levels with large z-components of the magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted here that we have not considered another important torsional angle parameter of X‐Co‐X‐Y ( ω ) as the ligands here are bidentate in nature and therefore ω does not vary much across the structures. It is observed that the axial and rhombic anisotropies ( D and E / D ) strongly depend on angle 2 θ and dihedral angle θ d …”
Section: Resultsmentioning
confidence: 99%
“…The resulting excitation energies are 952, 4657, and 4703 cm 21 which are very close to previously obtained SORCI values of 954, 4771, and 4771 cm 21 . [48,49] Hence the FIC MRCI method, implemented via the ORCA-AGE or comparable tools, is probably the most rigorous variational post-CASSCF treatment routinely applicable to chemically relevant molecules.…”
Section: Full Papermentioning
confidence: 99%